Multi-Stage Coordinated Planning Method for Transmission Network and Energy Storage Considering Carbon Trading Cost - Qiang LI; Yao WANG; Yingying HU; Xiaoming ZHENG; Linna ZHANG; Yongming JING (Zhongguo dianli)
The coordinated development of transmission network and energy storage is an important way to build a new type of power system. Traditional transmission and storage coordination planning often overlooks the error in the probability of clustering new energy output scenarios such as wind power, and the planning results are conservative. For this reason, this article first generates a typical scenario set by clustering the load demand and wind farm output under the annual cycle, and considers the error of scenario probability to establish an uncertain set of scenario probability distribution based on 1-norm and ∞ norm. Then, a multi-stage coordinated distributed robust programming model for transmission and storage is established with comprehensive objectives of transmission line investment cost, energy storage investment cost, operation cost, and carbon trading cost. The column and constraint generation (C&CG) algorithm is used to transform the multi-stage coordinated distributed robust programming model for transmission and storage into an iterative solution of the main and sub problems. The superiority of the proposed multi-stage coordinated planning method for transmission and storage was verified on an improved IEEE-30 node system.